The effect of physical activity in team-based project learning on collaboration skills - Mohammad Agus Prayitno; Sri Haryani; Sri Wardani; Nanik Wijayati; Bimacita Global (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Learning that emphasizes physical activity contributes to a person's ability to interact positively with others. One of the learning that emphasizes group-based physical activity is Team-based Entrepreneurship Project (TBEP) learning.